2019
DOI: 10.1024/1861-6186/a000509
|View full text |Cite
|
Sign up to set email alerts
|

Studiengangsübergreifendes Lernen im SimLab

Abstract: Zusammenfassung. Die Methode der Simulation bietet Lernenden die Möglichkeit ein planmäßiges Vorgehen in einem geschützten Rahmen, durchdacht und schrittweise für eine beruflich relevante Situation auszuprobieren. Dabei lernen sie, sowohl die Vorgehensweise zielführend einzusetzen als dabei auch eigene Erfahrung durch die Handlungsform zu reflektieren und somit professionelle Kompetenzen weiter zu entwickeln. Wie kann dieser hohe Anspruch annäherungsweise erreicht werden? Überlegungen hierzu und Schritte zur R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Both educational research in general and research in health professionals’ education in particular have shown that additional instructional support is needed for learning from challenging problems in complex learning scenarios ( 18 , 28 , 35 , 36 ). FINCA therefore suggests various support measures in the context of teaching and learning as important variables that may influence or moderate the observable collaborative activities.…”
Section: Structural Components Of Fincamentioning
confidence: 99%
“…Both educational research in general and research in health professionals’ education in particular have shown that additional instructional support is needed for learning from challenging problems in complex learning scenarios ( 18 , 28 , 35 , 36 ). FINCA therefore suggests various support measures in the context of teaching and learning as important variables that may influence or moderate the observable collaborative activities.…”
Section: Structural Components Of Fincamentioning
confidence: 99%